Vickers microhardness and indentation fracture toughness of tantalum sesquinitride, η-Ta2N3. Issue 1 (January 2016) - Bourguille, Judith; Brinza, Ovidiu; Zerr, Andreas
Abstract: Vickers indentation testing was applied to examine an additive-free monolithic sample of tantalum sesquinitride having orthorhombic U2 S3 type structure, η-Ta2 N3, synthesised at high pressures and temperatures. Crystallisation of η-Ta2 N3 in form of elongated crystals and a high bulk to shear modulus ratio of 2.3–2.6, considered as a qualitative criterion of malleability, suggest elevated fracture toughness for this ceramic material. Here we measured Vickers hardness, H V, indentation size effect, and fracture toughness, K Ic-if, as well as their dependences on the surface self-healing (densification) due to mechanical polishing for a sample with the residual porosity of p =0.14. H V of η-Ta2 N3 was found to exhibit a moderate indentation size effect and approach, for the porous sample, H V (1)=16(1) GPa at the maximal load. K Ic-if was measured to be 4.6(2) MPa m 1/2, comparable with the values reported for hexagonal Si3 N4 and SiC.